ADOLESCENT DIGITAL LITERACY AND ETHICS - Lubis, Rafly Aulia; Sinaga, Risky; Fauza, Aan (Transpublika Publisher, 2022)
Language is a means of communication among individuals. Along with the development of social media, aspects of communication using language are increasingly diverse. This diversity appears according to general agreement in community communication patterns. The tendency to produce new terms is very possible where communities have diverse backgrounds, both educational, economic, family and so on, as factors that produce new languages. This study uses a qualitative approach that presents research on the use of language in social media. The finding shows that new media and adolescence are both seen as something that is taking shape. The instability of these two things has a tendency to be mutually beneficial or even detrimental on the one hand. Early awareness of the characteristics of the new digital ethical world media in relation to adolescent users is expected to reduce the negative excesses of the impact it causes. Hence, literacy and ethics towards new media are the keys for teenagers to be able to enrich their identities and maintain their privacy.